ANALISIS KENDALA LITERASI DINI BAGI ANAK USIA 4-6 TAHUN DI PAUD - Monica Arningsari; Ida Dwijayanti; Sumarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the obstacles to early literacy in children aged 4-6 years in Early Childhood Education (PAUD) through a qualitative approach with research subjects who are children aged 4-6 years and 30 PAUD educators selected using purposive sampling. Data collection methods involve observation and interviews with PAUD educators as well as interactions with children aged 4-6 years. The data analyzed includes observations of children's literacy activities, interviews and educators' perceptions of the obstacles faced in supporting early literacy. The results of the research show that early literacy in PAUD has not been able to run optimally due to various obstacles, including many still narrow understanding of literacy, diverse human resources including psychological, social and environmental aspects. The discussion of findings links the results of the analysis to early literacy theory and provides insight into the factors that influence literacy development in early childhood in PAUD. The implications of this research contribute to the development of more effective early literacy education strategies in the PAUD environment.